Agreement No. 1 in the form of an Exchange of Letters between the United Kingdom of Great Britain and Northern Ireland and Ukraine to amend the Political, Free Trade and Strategic Partnership Agreement between the United Kingdom of Great Britain and Northern Ireland and Ukraine, London and Kyiv, 4 May 2022. ([2023-02-23]) - Unknown
No abstract available